Comparative Analysis of the Concept of Death in Turkish and Japanese Proverbs - Dogan, Guliz (European Scientific Journal, ESJ, 2024)
Death constitutes the last part of the life cycle. Although both being born and living are welcomed with joy by human beings, death brings pain and eternal unhappiness. This paper focuses on revealing how the concept of death, which contains deep sadness, is handled in Turkish and Japanese proverbs. Proverbs are stereotypes passed from one generation to another and are very important in reflecting the lifestyles and ways of thinking of the societies to which they belong. Proverbs are essential in transferring cultural knowledge because our ancestors created them with the accumulation and experience of many years. In this study, comparative analysis method is employed. Total of 127 proverbs, including 80 Turkish proverbs and 47 Japanese proverbs, are examined. They are grouped into death has causes, death as an unknown end, death has time to occur, grief for death, death is not welcomed, death occurs one time, death as a bad situation, understanding the value of things and people after death, death and animal, after death there is no meaning, comparing the wrong things with death, death relates to funerals and religious rituals, death is a relief and escape, and contradicting proverbs. As a conclusion, although Turkish and Japanese people have different cultural backgrounds, it is seen in proverbs that they have similar cultural values to death. All categories as mentioned above have similarities except the grief for death seen in Turkish proverbs but not in Japanese. The religious rituals that relate to death differ as both (Turks and Japanese) have different religions. Although there are expressions about Islam in Turkish proverbs, expressions about Buddhism are seen in Japanese proverbs.